2011
DOI: 10.1136/jnnp-2011-300909
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI reveals cortical thinning in amyotrophic lateral sclerosis

Abstract: Cortical thinning of the primary motor cortex might be a diagnostic marker for upper motor neuron degeneration in ALS. Relative thinning in temporal regions was associated with a rapidly progressive disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
134
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 45 publications
20
134
0
Order By: Relevance
“…The subcortical hypointense line corresponding to U-fibers appears smooth, and the gray-white junction, poorly demarcated ( Fig 1A, -B). When the M1 anatomy differed from such configurations, and namely the M1 deeper layers were particularly thin 23,29 and/or hypointense 9,30 ( Fig 1D, -E), images were judged as belonging to patients with ALS. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy in distinguishing patients and HS were calculated for each reader.…”
Section: Image Analysismentioning
confidence: 99%
“…The subcortical hypointense line corresponding to U-fibers appears smooth, and the gray-white junction, poorly demarcated ( Fig 1A, -B). When the M1 anatomy differed from such configurations, and namely the M1 deeper layers were particularly thin 23,29 and/or hypointense 9,30 ( Fig 1D, -E), images were judged as belonging to patients with ALS. Sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy in distinguishing patients and HS were calculated for each reader.…”
Section: Image Analysismentioning
confidence: 99%
“…Compared with VBM studies, SBM studies of patients with ALS uniformly report reduced cortical thickness in primary motor regions [28][29][30][31]. While SBM provides measures of cortical surface area and cortical volume, it has been demonstrated that cortical thickness is the key metric to detect changes in ALS [30].…”
Section: Volumetric Imagingmentioning
confidence: 99%
“…While SBM provides measures of cortical surface area and cortical volume, it has been demonstrated that cortical thickness is the key metric to detect changes in ALS [30]. Cortical thinning has been shown to be a consistent alteration that is specific to upper motor neuron degeneration in ALS.…”
Section: Volumetric Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological changes in amyotrophic lateral sclerosis (ALS) patients by structural MRI analysis 42,43 as well as sensorimotor functional connectivity changes in ALS patients 21 have been reported recently. In this work, as an example for application of the analysis methods WBSS and TFAS, twenty ALS patients were investigated by multiparametric MRI.…”
Section: Dti In Neurodegeneration (Motor Neuron Diseases)mentioning
confidence: 99%